Patella Height as Defined by Patella–Trochlear Articulation on MRI Scan—A Systemic Review of Current Evidence - Bajada, Stefan; Mandalia, Vipul (The Journal of Knee Surgery, 2019)
The objective of this study is to investigate what are the normal values, cutoff values, and optimal method of magnetic resonance imaging (MRI) scan for patella height focusing on patella–trochlear index (PTI). Electronic searches of MEDLINE (PubMed), Cumulative Index to Nursing and Allied Health Literature, Cochrane, Embase, ScienceDirect, and National Institute for Health and Care Excellence evidence up to April 2018 were completed. Eligibility criteria for selected studies included case-controlled studies, prospective cohort studies, cross-sectional and randomized controlled trials reporting on the use of MRI to evaluate direct patella height. Exclusions included animal or biomechanical/computational studies; interventional surgery such as knee arthroplasty, bracing, or realignment; and hereditary/congenital disease. A quality assessment of included studies was completed using the Methodological Index for Non-Randomized Studies (MINORS) Criteria. Sixty-four articles were identified which met the inclusion criteria. Following exclusions, 11 full-text studies were reviewed which reported direct measure of patella height. Nine studies reported the use of PTI. Two low power studies described PTI in normal healthy asymptomatic knee. Similarly, one study evaluated the effect of flexion and weight bearing on PTI values. The cutoff values varied between studies from <0.125 to <0.28 for patella alta and >0.50 to >0.80 for patella baja. This review found that currently, there are a very few studies on the assessment of PTI on MRI scan, with only two low powered studies on a true normal population. In view of this, there is a need for adequately powered studies to investigate patella height and PTI in asymptomatic healthy knees.
Keywords: patella alta; patella height; magnetic resonance imaging; patellofemoral joint; patella–trochlear index